Images of the Second World War in Austrian Literature after 1945 - Karl Müller (Studies in 20th & 21st Century Literature, 2007)
The author examines selected examples of post-1945 Austrian literature, asking what pictures of the Second World War they imparted and what role they played when, certainly from 1948 on, a certain image of history began to take shape in Austria against the background of the Cold War. This image involved a fade-out in particular of the racist nature of the war, and it had a collectively exonerating and distorting impact. Attention is paid to the stories and novels of former participants in the war and National Socialists, such as, for example, Erich Landgrebe, Erich Kern, Hans Gustl Kernmayr, Kurt Ziesel. A contrast is seen in the anti-war novel, Letzte Ausfahrt (Last Exit) (1952) by the former soldier Herbert Zand, who turns against the dominant image of history, as well as in Ingeborg Bachmann's use of war memories as a topic. The texts are read as a reservoir of selective memory: on the one hand they are critical, individual counter-memories and on the other hand, they make a positive contribution to the formation of the aforesaid collective image. One may say that a war of perception was fought around the Second World War; it was undoubtedly won in the immediate post-war years by those literary works that legitimized or at least trivialized the war. The critical voices of Herbert Zand, Gerhard Fritsch, and Ingeborg Bachmann were unfortunately the quieter ones and were not particularly successful in their time.
Keywords: Austrian literature; postwar; World War II; Second World War; Cold War; racism; race; Erich Landgrebe; Erich Kern; Hans Gustl Kernmayr; Kurt Ziesel; anti-war novel; Letzte Ausfahrt; Last Exit; Herbert Zand; Ingeborg Bachmann; war memories; memories; post-war; Gerhard Fritsch